(untitled) (Fiep Bulletin - online, 2015)
It is called for a fact in the current literature, that the aerobic training, by itself, without the control in its accomplishment, does not attend to the necessities destined. Such controls are carried through the heart rate, blood pressure, Subjective Perception of discomfort and effort, METs, and in some cases, the generated by Blood Lactate levels in the effort. The objective of this study was to compare the alterations of the physiological parameters (Cardiac Frequency, Arterial Pressure, Blood Lactate concentration, Double Product and Subjective Perception of Effort) of individuals that are not sedentary, when submitted to a test with two types of ergometers - treadmill and Transport (T). The model of this study was descriptive and correlative. The type of the sample was intentional and none probabilistic. Ten men participated in this research, with the average and standard deviation with ages between 27, 20 ± 6, 05 years, the average height and standard deviation of 1,76m ± 0,08m and body mass of 79,79kg ± 10,49kg. The analysis of the results was made by means of descriptive statistics and later inferential statistics. In the Subjection Perception of Effort the values in the Treadmill test had been bigger in the intermediate periods of training and the Transport in the first and the last periods of training. In relation to Blood Lactate they had been bigger in the Treadmill than the Transport during the test as in the recovery. Regarding to the Cardiac Frequency, the values observed in the Transport in average were smaller in relation to the one of the Transport. Based on the Arterial Pressure, the systolic, the average values were bigger in the Treadmill in relation to the Transport. But, in the Diastolic Arterial Pressure the average values for the Transport were bigger than the values from the Treadmill. As for the Double Product, it showed bigger results for the Treadmill when collated to the results gotten from the Transport. Even not being the main object of the study it fits to stand out that the information proceeding from the kinetic of the Cardiac Frequency in the 2 ergometers propitiated the attainment of an equation that relates the Cardiac Frequency gotten in the Treadmill test with the one that must be used in the work carried through with the Transport in the same emphasis.